COMPARING KWL AND SQ3R MODELS ON ENHANCE JUNIOR HIGHSCHOOL STUDENTNS’ READING COMPREHENSION - Thaharnunu, Margaretha Maurits; Sulistyanto, Irwan; Muchyidin, M. Syaichul (Universitas Muhammadiyah Metro, 2025)
This study examines the comparative effectiveness of the KWL (Know-Want-Learned) and SQ3R (Survey, Question, Read, Recite, Review) methods in enhancing reading comprehension among 7th-grade students at SMPN 2 Ngadiluwih. The research was motivated by the lack of consensus on the superiority of both methods and the need to account for classroom dynamics and student motivation, factors often overlooked in prior studies. Participants included 68 students, divided into two groups: an experimental group (KWL) and a control group (SQ3R), with reading comprehension scores as the dependent variable, measured via a 20-item multiple-choice test. The objective was to compare the impact of both methods while identifying external factors such as student engagement and teacher competency. A quasi-experimental design with a pre-test and post-test revealed significant improvements in reading comprehension for both methods. However, no statistical difference was found (p-value = 0.914). Data analysis using the Kolmogorov-Smirnov normality test, homogeneity test, and independent t-test in SPSS 27 confirmed that implementation success was influenced by the classroom environment, such as the presence of peer tutors in the SQ3R group, which fostered a conducive learning atmosphere. The study concludes that the KWL method is suitable for simpler texts with high student motivation. In contrast, the SQ3R method is more effective for in-depth analysis with structured guidance. Practical implications include recommendations for teachers to combine both methods based on student needs, the necessity of research-based reading strategy training, and future exploration of technology integration in pedagogical approaches.